2010
DOI: 10.1371/journal.pone.0014332
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin Controls CBP Levels in the Adult Drosophila Central Nervous System

Abstract: BackgroundDominant mutations in both human Presenilin (Psn) genes have been correlated with the formation of amyloid plaques and development of familial early-onset Alzheimer's disease (AD). However, a definitive mechanism whereby plaque formation causes the pathology of familial and sporadic forms of AD has remained elusive. Recent discoveries of several substrates for Psn protease activity have sparked alternative hypotheses for the pathophysiology underlying AD. CBP (CREB-binding protein) is a haplo-insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Using a ubiquitous driver, we first confirmed that our Psn shRNA lines result in 80-90% reduction of mRNA levels (Figure 1) and recapitulate developmental phenotypes of Psn germ-line mutant flies (Struhl and Greenwald 1999;Chung and Struhl 2001;Mahoney et al 2006). Consistent with notching wings in Notch heterozygous mutant flies, and in wing-specific Notch or Psn KD flies (Boyles et al 2010;Casso et al 2011), wing disc-specific expression of Psn shRNA leads to similar wing phenotypes at varying severity, allowing selection of the most effective Psn shRNA line (Figure 2). Selective neuronal expression of two independent Psn shRNA lines beginning at embryonic stages caused earlier lethality, rough eye phenotypes, and severe climbing defects (Figure 3 and Figure 4), and these phenotypes were partially rescued by expressing a Drosophila Psn transgene ( Figure 5).…”
Section: Discussionsupporting
confidence: 65%
“…Using a ubiquitous driver, we first confirmed that our Psn shRNA lines result in 80-90% reduction of mRNA levels (Figure 1) and recapitulate developmental phenotypes of Psn germ-line mutant flies (Struhl and Greenwald 1999;Chung and Struhl 2001;Mahoney et al 2006). Consistent with notching wings in Notch heterozygous mutant flies, and in wing-specific Notch or Psn KD flies (Boyles et al 2010;Casso et al 2011), wing disc-specific expression of Psn shRNA leads to similar wing phenotypes at varying severity, allowing selection of the most effective Psn shRNA line (Figure 2). Selective neuronal expression of two independent Psn shRNA lines beginning at embryonic stages caused earlier lethality, rough eye phenotypes, and severe climbing defects (Figure 3 and Figure 4), and these phenotypes were partially rescued by expressing a Drosophila Psn transgene ( Figure 5).…”
Section: Discussionsupporting
confidence: 65%
“…In mammalian models, these functions include stabilizing the binding of CTNNB1 and GSK3β, where Alzheimer disease causing mutations result in reduced stability of CTNNB1 [18,19,25,26], and in endoplasmic reticulum (ER) calcium regulation [27,28]. In D. melanogaster, presenilin proteins have been found to modulate the levels of CREBBP (cyclic-AMP Response Element Binding protein) independently of proteolytic activity [29]. A similar non-proteolytic function for presenilin proteins or the γ-secretase complex has also been proposed in both C. elegans [30] and the moss P. patens [20].…”
Section: Introductionmentioning
confidence: 99%
“…Kilgore, et al (2010), for example, demonstrated that memory deficits in the APPswe/PS1dE9 double-transgenic mouse model are reversed by HDAC1 inhibitor administration. CBP protein expression is decreased in a forebrain-specific double presenilin conditional knockout mouse (Saura, et al, 2004), and in flies, CBP levels in the central nervous system are reduced in the absence of presenilin (Boyles, et al, 2010). Furthermore, Rouaux, et al (2003) and Saha, et al (2009) found that CBP levels are decreased during neuronal apoptosis and that increasing expression can protect against toxic insults.…”
Section: Discussionmentioning
confidence: 99%